2012
DOI: 10.1039/c2ee21327c
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of domain size, domain purity and domain interfaces to the performance of bulk-heterojunction organic photovoltaics

Abstract: Groves, C. (2012) 'The relative importance of domain size, domain purity and domain interfaces to the performance of bulk-heterojunction organic photovoltaics.', Energy and environmental science., 5 (6). pp. 7657-7663. Further information on publisher's website:http://dx.doi.org/10.1039/C2EE21327CPublisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
166
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(172 citation statements)
references
References 58 publications
(121 reference statements)
6
166
0
Order By: Relevance
“…A Monte Carlo charge transport model similar to that reported elsewhere 29 was used to simulate  GS . Models of this type have been shown to agree quantitatively with J-V curves of polymer bilayer OPV devices with abrupt 30 and roughened 31 interfaces.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…A Monte Carlo charge transport model similar to that reported elsewhere 29 was used to simulate  GS . Models of this type have been shown to agree quantitatively with J-V curves of polymer bilayer OPV devices with abrupt 30 and roughened 31 interfaces.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…However, it has latterly been argued that the Braun expression incorrectly assumes that separation and recombination follow exponential kinetics [109]. However, from a pragmatic point of view, it is difficult to be critical of the Braun model as analytical expressions which more correctly account for transport environment in OSCs [110][111][112] still do not encompass all of the potentially relevant physics [113,114]. Given that the geminate recombination model will (almost) inevitably not include physics relevant to the OPV in question, it is perhaps safest to consider the recombination rate in such models as a fitting parameter that is indicative of how good or bad GR is, but having no further quantitative meaning [73].…”
mentioning
confidence: 99%
“…Later experiments and modelling by Yan et al [377] on non-annealed and annealed bilayer OPVs, such that the former had a sharper interface than the latter, supported the notion that interface morphology was important in determination of GR. Both Lyons et al [114] and Gagorik et al [382] showed that impure domains, where they lead to disconnected islands of donor material in the acceptor phase and vice versa, can act as charge recombination centres. This suggests that molecularly mixed phases reported in some in high performance OPVs [343,344] support ambipolar charge transport [388], since if complete charge transport networks for both electrons and holes were not present in the mixed phase, trapping and recombination would occur.…”
mentioning
confidence: 99%
See 2 more Smart Citations